Genomic information and a person's right not to know: A closer look at variations in hypothetical informational preferences in a German sample. - Laura Flatau; Markus Reitt; Gunnar Duttge; Christian Lenk; Barbara Zoll; Wolfgang Poser; Alexandra Weber; Urs Heilbronner; Marcella Rietschel; Jana Strohmaier; Rebekka Kesberg; Jonas Nagel; et al. (PLoS ONE)
In clinical practice and in research, there is an ongoing debate on how to return incidental and secondary findings of genetic tests to patients and research participants. Previous investigations have found that most of the people most of the time are in favor of full disclosure of results. Yet, the option to reject disclosure, based on the so-called right not to know, can be valuable especially for some vulnerable subgroups of recipients. In the present study we investigated variations in informational preferences in the context of genetic testing in a large and diverse German sample. This survey examined health care professionals, patients, participants of genetic counseling sessions and members of the general population (N = 518). Survey participants were assessed regarding their openness to learning about findings under various hypothetical scenarios, as well as their attitudes about the doctor-patient-relationship in a disclosure situation and about informational transfer to third parties. While the majority of participants wanted to learn about their findings, the extent of support of disclosure varied with features of the hypothetical diagnostic scenarios (e.g., controllability of disease; abstract vs. concrete scenario description) and demographic characteristics of the subjects. For example, subjects with higher levels of education were more selective with regards to the kind of information they want to receive than those with lower levels of education. We discuss implications of these findings for the debate about the right not to know and for the clinical practice of informed consent procedures.